Marketing strategy with e-commerce (Case study: UMKM Abon Ikan Kardina) Tanjungpinang City - Risandi, Ari; Hafsar, Khairul; Tetty, Tetty (Nekton, 2024)
Entrepreneurs are currently implementing marketing strategies to sell goods and services through e-commerce systems. E-commerce is used for business development in marketing. One of the Micro, Small, and Medium Enterprises (MSMEs) that use the e-commerce system is the Abon Ikan Kardina MSME. Abon Ikan Kardina has used e-commerce in its marketing strategy efforts but has not been effective because offline sales are more than through e-commerce. The research objectives were to identify the implementation of marketing strategies through e-commerce at MSME Abon Ikan Kardina and formulate marketing strategies through e-commerce at MSME Abon Ikan Kardina. The research was conducted from March to May 2023 at the Abon Ikan Kardina UMKM. The research method used was descriptive qualitative, using SWOT and AHP analyses. The results showed that implementating marketing strategies through e-commerce at MSME Abon Ikan Kardina is seen in several uses of e-commerce applications and social media in the form of Shopee, Facebook, Instagram, and WhatsApp. Based on the results of SWOT and AHP analyses, it is known that implementing marketing strategies through e-commerce at Abon Ikan Kardina MSMEs is seen from the use of several e-commerce and social media applications such as Shopee, Facebook, Instagram, and WhatsApp. The Abon Ikan Kardina MSMEs' product content supports these applications' use. Four priority strategies in the formulation of marketing strategies through e-commerce at Abon Ikan Kardina MSMEs are: (1) improving and maintaining product quality, (2) providing good product quality information to be trusted in the market, (3) providing training for human resources to understand e-commerce and bookkeeping, and (4) regularly updating content on each social media account.